EFFICACY AND SAFETY OF FORMOTEROL IN CHILDREN WITH BRONCHIAL ASTHMA EXACERBATIONS - S.V. Zaitseva; O.V. Zaitseva; N.V. Aleksandrina; T.V. Praznikova; T.I. Rychkova; S.I. Bardennikova; E.V. Kulikova; O.B. Dovgun; M.A. Kazantseva; O.B. Voronina; T.P. Rubtsova (Вопросы современной педиатрии, 2008)
Efficacy and safety of long acting 29 agonist formoterol (foradil aerolizer) was investigated in comparative study. 30 pediatric patients (6–16 years old) with bronchial asthma were treated with formoterol. 100 ?g of salbutamol by metered9dose inhaler was administered to control group of children (n = 30). The bronchodilating effect of formoterol was comparable to that of short acting 29 agonist salbutamol. Maximal bronchodilating action was registered in 2–4 hours after inhalation and lasted out more then 12 hours. For moterol aerolizer can be easily applicated and allows to carry out doctor's recommendations and to increase the effectiveness of treatment. Formoterol aerolizer allows making greatly less mistakes in inhalation technique then salbutamol in metered dose inhaler. Authors made a conclusion that for moterol can be used as a rescue treatment in children with bronchial asthma upwards 5 years old treated with appropriate basis regimens. Key words: children, bronchial asthma, formoterol, aerolizer.